Deep Web e segurança da informação: uma análise e seus impactos na sociedade e nas organizações - Kozakiewicz, Dilmar José (2018)
This work seeks to show the increasingly intense presence of networks in our lives. It brings a discussion about the obscure internet, how it can be used for both good and evil, and the security it gives us when it comes to privacy. Through qualitative research, using as its main source the network itself, we sought to show how this theme brings changes in our lives, in organizations and in society in general. It also seeks to show characteristics of the open internet and the Deep Web, as an alternative to privacy, but also as an environment conducive to illegal actions. The theme "Deep Web" itself is dynamic and hardly fits the literatures of already established networks; is a subject constantly updated. Through the raised sources we also sought to make a deductive analysis of what is expected with natural or logical evolution on everything that involves the subject. We also deal with the issue of Information Security, establishing a parallel of the computerization of companies with the advent of networks and their growth. And finally leave as a legacy a discussion, which we believe has not yet come to a term, about what awaits us in the future, when we refer to the state of the art of information technology and what it covers: networks, anonymity, security and privacy.